2x+5-4(x+4)=-3(x-3)

Simple and best practice solution for 2x+5-4(x+4)=-3(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+5-4(x+4)=-3(x-3) equation:



2x+5-4(x+4)=-3(x-3)
We move all terms to the left:
2x+5-4(x+4)-(-3(x-3))=0
We multiply parentheses
2x-4x-(-3(x-3))-16+5=0
We calculate terms in parentheses: -(-3(x-3)), so:
-3(x-3)
We multiply parentheses
-3x+9
Back to the equation:
-(-3x+9)
We add all the numbers together, and all the variables
-2x-(-3x+9)-11=0
We get rid of parentheses
-2x+3x-9-11=0
We add all the numbers together, and all the variables
x-20=0
We move all terms containing x to the left, all other terms to the right
x=20

See similar equations:

| b/11-9b/11=48/11 | | 3m÷4-m÷12=7/7 | | 2x-3.1=5x-51/2 | | 4y-36×=28 | | 81/3y=-8 | | 4n+24+5n+21=180 | | 8x16=8 | | 2/3{2x-12}=10 | | -12+p=-38 | | -2r+1=9 | | -22-6x=-3(-6+2)+8 | | 4​(x-6)+4=6x-6 | | 7+x=1/2(2x-6) | | 12=2t+4 | | 4.6=7.3-0.9x | | 4-7n=-(8n+4)=2 | | 3g+2=g | | 2h−14=-4 | | -1.05x+9.2=-9.6 | | 2r+1=-9 | | b/2-1=2 | | -48=-6(2n+8)+12 | | 3(3r-2)=5r-34 | | x=12=4x-6 | | 18=3+3b | | 32π=8πx | | 18t+12=t+46 | | 0.13y=0.89 | | 2x+14.5=21.4 | | 5÷6x+7=17 | | 25=h+(-18) | | -11-4x=-31 |

Equations solver categories